2006
DOI: 10.1111/j.1467-6486.2006.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Authorship in Management and Organizational Studies: An Empirical and Network Analysis*

Abstract: In recent decades there has been growing interest in the nature and scale of scientific collaboration. Studies into co-authorship have taken two different approaches. The first one attempts to analyse the reasons why authors collaborate and the consequences of such decision (Laband and Tollison, 2000). The second approach is based on the idea that co-authorship creates a social network of researchers (Barabási et al., 2002;Moody, 2004;Newman, 2001). In this study we have carried out an exploratory analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
439
4
61

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(522 citation statements)
references
References 53 publications
(132 reference statements)
18
439
4
61
Order By: Relevance
“…In many ways, we attempted to model our project after this effort. Additionally, scholars have used networks to explore the history of English 13 , international relations 14 , Marketing 15 , and management and organization studies 16 . In line with the current study's aims, research demonstrates that networks can be used to discover a field's "peculiarities" in terms of why authors collaborate, lineages between authors, and how collaboration affects and is affected by journal outlet selection.…”
Section: Network As Analytic Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…In many ways, we attempted to model our project after this effort. Additionally, scholars have used networks to explore the history of English 13 , international relations 14 , Marketing 15 , and management and organization studies 16 . In line with the current study's aims, research demonstrates that networks can be used to discover a field's "peculiarities" in terms of why authors collaborate, lineages between authors, and how collaboration affects and is affected by journal outlet selection.…”
Section: Network As Analytic Toolmentioning
confidence: 99%
“…Previous studies have demonstrated that coauthoring improves the quality of submissions 28 , and increases the probability of acceptance. Furthermore, acceptance and allocation of editorial space is influenced by the affiliations among authors, editors, and coeditors, which begins in graduate school and continues in current employment 29,30,31 . Analyzing the preliminary data we have put together an initial network map of collaboration.…”
Section: Collaboration/co-authorshipmentioning
confidence: 99%
“…Primeiro, significa a validação dos seus trabalhos, dado que os artigos publicados em periódicos com revisão pelos pares são considerados certified knowledge (Miller, 2006;Acedo, Barroso, Casanueva, & Galán, 2006). Segundo, é pela publicação que se dissemina o novo conhecimento gerado (Bedeian, 2004;Gondim, 2004;Miller, 2006;Elson & Brouard, 2012).…”
Section: Introductionunclassified
“…Assim, não é estranho que vários autores, em diversas disciplinas, se tenham debruçado sobre diferentes facetas da publicação científica, focando aspectos como as dificuldades de publicação (Serra, Fiates & Ferreira, 2008), as redes de coautoria (Barabási;Jeong;Néda;Ravasz;Schubert & Vicsek, 2002;Moody, 2004;Acedo et al, 2006), o que fazer para aumentar a probabilidade de conseguir publicar (Moody, 2004;Sparrowe & Mayer, 2011;Geletkanycz & Tepper, 2012;Zhang & Shaw, 2012), a rejeição (Gans & Shepherd, 1994;Beyer, Chanove & Fox, 1995;Byrne, 2000), as perspectivas dos revisores (Singh, 2003;Swanson, 2004) e dos editores (Radford, Smillie, Wilson, R. & Grace, 1999;Pinho, 2005), os riscos à saúde da carreira do pesquisador (De Meis, Velloso, Lannes, Carmo & De Meis, 2003), o produtivismo (Sguissardi & Silva Jr., 2009), a relevância e rigor da produção científica em Administração (Mascarenhas, Zambaldi, & de Moraes, 2011), as taxas de aceitação dos artigos nos periódicos (Sugimoto, Larivière, Ni & Cronin, 2013), a revisão pelos pares (Armstrong, 1997;Byrne, 2000;Dahdouh-Guebas, Ahimbisibwe, Van Moll & Koedam, 2003;Miller, 2006;Blackburn & Hakel, 2006;Raelin, 2008) e a rejeição direta ou desk rejection pelos editores (Craig, 2010;Ahlstrom, 2010).…”
Section: Introductionunclassified
“…또한 공동출판을 통 하여 후속적으로 기존 관계의 강화 또는 새로운 공동출 판 관계의 형성으로 이루어질 수도 있다 (Acedo et al, 2006). 즉 공동출판에 참여하는 연구자들 간의 사회적 관계의 구성이 현재 연구 자체는 물론 그 후의 연구 활 동, 나아가 해당 학문분야의 연구 활동 전반에 영향을 줄 수 있다는 추론도 가능해진다 (최영훈, 이강춘, 2009) …”
unclassified